2020
DOI: 10.3382/ps/pez503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary methionine plus cysteine levels on growth performance and intestinal antibody production in broilers during Eimeria challenge

Abstract: Research has shown that methionine+ cysteine (M+C) requirements may be higher when chickens are infected with Eimeria app. In a 4 × 2 factorial design, broilers (11 to 21 D) were fed one of 4 corn–soybean meal-based diets containing either 0.6, 0.8, 0.9, or 1.0% standardized ileal digestible (SID) M+C; on day 14, broilers from each diet were gavaged with either phosphate-buffered saline (PBS) or a commercial coccidiosis vaccine (at 100 × vaccine dose) which provide a mixture of live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
(24 reference statements)
4
23
1
Order By: Relevance
“…In agreement with other published work (Ohta and Ishibashi 1995;Conde-Aguilera et al 2013;Rehman et al 2019;Ghavi et al 2020;Ren et al 2020;Zarghi et al 2020b), in the current study increasing supplemental DL-Met improved growth performance (Table 3 and Figures 1-3). Methionine supplementation improves dietary amino acid balance and consequently promotes LBW and WG growth by increasing protein synthesis and decreasing fat synthesis, leading to enhanced feed efficiency.…”
Section: Growth Performancesupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other published work (Ohta and Ishibashi 1995;Conde-Aguilera et al 2013;Rehman et al 2019;Ghavi et al 2020;Ren et al 2020;Zarghi et al 2020b), in the current study increasing supplemental DL-Met improved growth performance (Table 3 and Figures 1-3). Methionine supplementation improves dietary amino acid balance and consequently promotes LBW and WG growth by increasing protein synthesis and decreasing fat synthesis, leading to enhanced feed efficiency.…”
Section: Growth Performancesupporting
confidence: 93%
“…Methionine is not only the first limiting amino acid for broiler growth but has also been shown to play vital roles in immune function. Methionine is a precursor of polyamines required for immune cell proliferation, induction/regulation of inflammation, and pathogen recognition (Ren et al 2020). Met deficiency may impair the immune system and metabolic disorders (Rehman et al 2019).…”
Section: Immune Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the use of the 100% TSAA diet, obtained by the addition of Met to the diet, could partially ameliorate the negative effect of the Eimeria challenge on feed efficiency during the challenge phase. Ren et al. (2019) , however, did not find interactions between the Eimeria challenge and TSAA levels and concluded that the supplementation of TSAA at levels higher than 0.80%, on a standardized ileal digestibility basis, was not able to counteract the negative effects of a cocci infection.…”
Section: Discussionmentioning
confidence: 96%
“…Unexpectedly, we did not observe many interactions between the Eimeria challenge and TSAA treatments. This finding could be an indication that 1) there was no change in the TSAA requirement when broilers were infected with Eimeria ( Murillo et al., 1976 ; Willis and Baker, 1981 ; Ren et al., 2019 ) and 2) the supplementation of Met or TSAA alone was not sufficient to mitigate the negative effects of an Eimeria infection on growth and intestinal health ( Ren et al., 2019 ). Nevertheless, our overall results showed that the Eimeria challenge negatively affected growth performance, intestinal histomorphology, and nutrient digestion; impaired the antioxidant system; and modulated the expression of TJP genes throughout the experimental period.…”
Section: Discussionmentioning
confidence: 99%